Public policies for the promotion of horticulture: the case of Algarve´s citrus. - Madeira, Emília (2011)
This research approaches some factors that have been affecting the competitiveness faced by the Algarve’s citrus culture since the European Single Market came into force and before a more and more global economy. As it is already known, in a global economy any competitive strategy must have underlying quality(ies). These are understood as the capacity to satisfy the market considered as a whole of the main types of agents at the different levels of Algarve’s citrus system. So, the main object of this work is to identify eventual (technical and institutional) mal-functions concerning the Algarve citrus system, that can fail either directly or indirectly to meet the principal clients/consumers’ expectations. The study took into account the general context where the Algarve’s citrus culture is inserted. The aim is to identify the constraints faced by the sector in order to understand the main clients, suppliers and competitors’ behaviours. The results have allowed us to characterize the quality attributes considered as determinants when the citrus fruits are acquired, namely the Algarve’s citrus, by the national consumers as well as by the main distribution channels, in case they are presented in the market as differentiated or undifferentiated. The facts identified in the empirical research indicate that limitations of technical and institutional order can make unfeasible or strongly condition the capacity of the Algarve citrus culture (production subsystem) to meet the market requirements. The conclusions reached for the development of the Algarve citrus culture, were based on Hayami and Ruttan´s “induced technical and institutional innovation” theory (1998). We think we have given a contribution towards the definition of strategies for the Algarve’s citrus culture development, bearing in mind both the market and the available resources.